Community-Based Physical Activity Interventions for Individuals with Moderate to Severe Traumatic Brain Injury: Scoping Review Protocol - Quilico, Enrico; Swaine, Bonnie; Alarie, Christophe; Colantonio, Angela (JMIR Research Protocols, 2021)
BackgroundLong-term physical, cognitive, and psychosocial problems resulting from moderate to severe traumatic brain injury (TBI) can prevent individuals from returning to preinjury lifestyles because of significant challenges with employment, leisure, and relationships. While physical activity (PA) is proposed as a cost-effective method to alleviate problems after moderate to severe TBI, there is no review to date that synthesizes the evidence for PA in the community-based context. Further, although sex- and gender-based considerations in research are considered requisite to good science, there is no review on PA and TBI that has included this explicit focus. ObjectiveThe purpose of this review is to map and synthesize the current evidence identified through a systematic search of community-based PA interventions for individuals of all ages with moderate to severe TBI and provide an overview of that evidence by asking the following research questions: (1) what are the characteristics of community-based PA programs for individuals with moderate to severe TBI, (2) what are the reported health-related outcomes and measurement tools used to evaluate them, and (3) what considerations have been given to sex and/or gender? MethodsSearches will be conducted of six academic databases for peer-reviewed articles. Two reviewers will independently screen the articles for inclusion and extract data for the analysis. The extracted data will be coded according to the Consensus on Exercise Reporting Template checklist and the Template for Intervention Description and Replication checklist to provide sufficient detail for replication. ResultsThe abstract screening was completed by two reviewers and the extracted data were analyzed. A qualitative synthesis and description of community-based PA interventions for individuals with moderate to severe TBI will be provided. ConclusionsThis scoping review will generate new knowledge from published and publicly available literature. Dissemination of the results will include activities related to knowledge transfer for community-based PA after moderate to severe TBI for future research and practice. Evidence-based recommendations, future directions, potential limitations, use of online/digital components, and the possible need for a systematic review will be discussed as well. International Registered Report Identifier (IRRID)DERR1-10.2196/24689